Health Conditions and Social Interactions - Diana Pacheco Barzallo (University of Neuchâtel, Institute of Economic Research (IRENE), 2011)
This paper evaluates the impact of an antipoverty program on the health condition of individuals. The program combines a cash transfer with financial incentives for positive behavior to poor families. Its main purposes are to improve the living conditions of eligible households and to promote their investment in their children through school attendance and the provision of basic health services. Since the design of the program includes information on eligible and ineligible families, it is possible to evaluate its direct effect as well as its indirect effect. While the direct impact is measured by the effect of cash grants on eligible individuals, its indirect impact is estimated by the effect generated for the treated neighbors on their non-treated peers. The results show that eligible and ineligible individuals significantly improved their health status due to the program's interventions: the sickness incidences decreased, the sickness spell was reduced, and people seemed to be able to manage normal activities with less difficulty. Thus anti-poverty programs, despite the fact that constitute a big weight in the public finance of a country, have an important multiplicative effect on the population. It not only generates, in the short run, an increase in the demand for health services but also changes in a positive way the behaviour of people by educating them on the importance of health and nutrition. This result will impact treated and non-treated families in the long run due to the high interaction that characterizes poor societies: families are learning from others.
Keywords: C93; I12; I28; I38; 330; Randomization; experimental design; social interactions